The Secret Sauce of Development Professionals: Tools for Assessing TOR Potential to Source Scalable Learning Interventions - Barton, Adam (Research on Improving Systems of Education (RISE), 2023)
Terms of reference (TORs) play an outsized role in driving scalable ed ucational programming. These procurement documents shape, constrain, a nd signal programme priorities and possibilities. Successful funders a nd implementers across the globe hold rich processual knowledge about this documentation, which they use to draft and assess TORs. This proj ect explores such best-practice knowledge around TOR review, seeking t o support the design and implementation of educational programmes that can improve learning at scale in developing contexts.